Multimodal 3D characterization of voids in shock-loaded tantalum: Implications for ductile spallation mechanisms. (15th August 2021) - Francis, Toby; Rottmann, Paul F.; Polonsky, Andrew T.; Charpagne, Marie-Agathe; Echlin, McLean P.; Anghel, Veronica; Jones, David R.; Gray, George T.; De Graef, Marc; Pollock, Tresa M.
Graphical abstract: Abstract: Predicting the failure of crystalline materials at high strain rates requires knowledge of the underlying failure mechanisms and their dependence on microstructure. In this study, a 3D-EBSD characterization experiment is performed on high-purity tantalum prior to and after partial spallation by plate impact, which allows for the statistical assessment of the microstructural neighborhoods surrounding incipient voids. In analyzing the resulting dataset containing 5884 grains and 467 voids, it is observed that the voids were roughly spherical and consistent in size throughout the spalled material. The voids are most likely to reside at quadruple points, at triple junctions, at grain boundaries, and within grains, in decreasing order of prevalence. Moreover, voids tend to form at grain boundaries with high degrees of plastic incompatibility, growing into the plastically soft grain but orienting primarily with or perpendicular to the loading direction. The statistics from these analyses of 3D microstructural data support dynamic cavitation models for ductile spallation.